Archivpflege im schlesischen Erzbistum Breslau 1936 bis 1939 - Maik Schmerbauch (Wrocławski Przegląd Teologiczny)
The article is based on unexplored records from the Ecclesiastical Archives of the archdiocese Wroclaw and also but minor from Katowice. In 1936 cause of the political treat of the Nazis regime to the Catholic Church in Germany the archdiocese Wroclaw under its longtime leader and bishop Cardinal Adolf Bertram begun to establish a strategy to protect the ancient records and collections in the almost 1000 parishes against the visible treat of unallowed access of Nazi people to it who would use the information for the racist ideology. Therefore the curia of Wroclaw 1936 released special orders and pronounced dozens of archival experts for the areas of parishes. They began to organize the classification and indexing of the old records on special index lists. Also records have been transferred to the big Ecclesiastical Archive to Wroclaw for their archival protection. Cardinal Bertram prohibited permanently the parishes not to allow any public access to their records. Surprisingly it was possible to establish from 1936 to 1939 a professional relationship between Wroclaw ecclesiastical Archivists and German State Archives in Wroclaw which was an advantage for the church records protection even until wars ended in 1945.